HUBUNGAN MUTU PELAYANAN PERAWAT DENGAN KEPUASAN PASIEN di RUANG RAWAT INAP RUMAH SAKIT SYAFIRA PEKABARU TAHUN 2018 - Yesica Devis (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2019)
Patient satisfaction in the inpatient room is very important to be noticed due to become the indireclyy driving factor for patient's health by improving the quality of service such as reliability, guarantee, physical proof, empathy, and responsiveness. The purpose of this research was to know the relation between Reliability, Assurance, Tangibles, Emphaty, and Responsiveness (Patience and Concern) with Patient Satisfaction. The research type was quantitative with cross sectional design. The sample in this research was 99 in patients at Syafira Hospital Pekanbaru which was choosen by using simple random sampling technique. The data were collected by using questionnaire and observation. The analysis used univariate and bivariate analysis with Chi-Square statistical test (p = 0,05). The results showed that there was a relation between reliability (p value = 0.001 and= OR value 79,625), Guarantee (p value 0.001 and OR 142,857), Physical evidence (p value = 0.001 and OR value 6.578), Empathy (p value = 0.001 and OR 93,333), Power Response (p value = 0,001 and OR 170,833) with Patient Satisfaction. The advice for nurses is all of the nurses should be able to provide excellent service with a sincere intention to give a positive impression on the quality of nursing services and improve patient satisfaction. Recommendation for Syafira Pekanbaru Hospital is Hospital management of this hospital need an improving of the quality of nursing services in order to fullfil patient satisfaction.